Stakeholder Analysis Approach: Who Is Authorized to Regulate the National Health Insurance Benefits? - Tisno Leksani Tunjungwulan; Alberto Daniel Hanani (IPTEK Journal of Proceedings Series, 2019)
BPJS Kesehatan (Badan Penyelenggara Jaminan Sosial Kesehatan) is an agency that liable to organize the nationalhealth security system in Indonesia. The health services director of BPJS Kesehatan has issued three regulations as an effort to control deficits which currently hit since 2014. The issuance of the regulations reaped controversy over its contents governing the limitation of health benefits that assured by BPJS Kesehatan. Besides that, BPJS Kesehatan has assumed not an authorized institution to issue that policy. This study aims to analyze the issuance of the regulations as a public policy. Data collection is obtained by in-depth interviews with top-level management, literature review and observation. Stakeholder analysis used to find out where the position of BPJS Kesehatan in the national health security system environment is. It will help in carrying out its functions and roles to succeed that program. Through stakeholder analysis is known that the government and the participants are the primary stakeholders of the national health security system. While BPJS Kesehatan is an agent representing the government providing health benefits to the participants. BPJS Kesehatan is not the primary stakeholder but secondary stakeholder, then the determination of any health benefits provided to the participants is an authority of the government rather than BPJS Kesehatan. Inaccuracy in the reading relationship between stakeholders could be at risk for BPJS Kesehatan in making a strategic decision. BPJS Health's lack of understanding of its authority, lead to ineffective decision-making and policies. The ineffectiveness of policies or decisions makes the goals of BPJS Health as providers of national health security programs difficult to achieve. By understanding the limits of its authority, BPJS Kesehatan able to take strategic steps according to the company's goals